2017
DOI: 10.1149/2.0521706jes
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a Hydrogen-Vanadium Reversible Fuel Cell

Abstract: Hydrogen-vanadium reversible fuel cells were tested using a Pt/C hydrogen electrode, carbon vanadium electrode and interdigitated flow fields at both electrodes. Vanadium electrolyte flow rate was varied to study its effect on mass transport performance. Two types of vanadium electrodes were explored, a single layer of high surface area carbon nanotube (CNT) electrode and three layers of nitric acid-treated carbon paper. Finally, four types of Nafion membranes were examined to determine the effect of membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Amongst the organic redox materials reported in the literature, the redox potential of BQDS is relatively high and this may mean that applying an electrode with a large surface area/ porosity in a high concentration of the electrolyte is expected to result in high current and power densities. As a consequence, we coupled this redox species with the hydrogen evolution/ oxidation reaction (HER/HOR) that is widely being studied in the literature 15,17,56 for RFC applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the organic redox materials reported in the literature, the redox potential of BQDS is relatively high and this may mean that applying an electrode with a large surface area/ porosity in a high concentration of the electrolyte is expected to result in high current and power densities. As a consequence, we coupled this redox species with the hydrogen evolution/ oxidation reaction (HER/HOR) that is widely being studied in the literature 15,17,56 for RFC applications.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] However, vanadium is a rare element so the capital cost of the redox material is a big obstacle for the large-scale commercialisation of the VRFB. [15][16][17][18][19] The energy cost of a VRFB is $320 per kW h whilst the target set by the U.S. Department of Energy (DOE) is $100 per kW h, with almost 50% of the price being dominated by the cost of the electrolyte. 20,21 In response to the price sensitivity of vanadium, various redox-active species have been investigated and suitable ones tailored to lower the cost of RFB redox materials.…”
Section: A Introductionmentioning
confidence: 99%
“…This higher performance could be attributed to an improved transport of active species to and from the porous electrode. Dowd et al 13 reported similar performance at an initial SOC of 90% with a cell configuration consisting of a carbon paper cathode, a Pt coated carbon paper anode and a N115 membrane. A peak power density of 1680 W m −2 at a current density of 2700 A m −2 and a limiting current density above 3500 A m −2 for a flow rate of vanadium electrolyte of 12 mL/min were reported.…”
Section: Energy Efficiency (η E )mentioning
confidence: 89%
“…A fuel cell startup procedure was carried out to ensure the membrane was properly hydrated prior to testing. The startup procedure consisted of cycling the fuel cell between discharge (0.6 V) and charge modes (1.3 V) every 10 min for more than 12 h. 8 Polarization curves were obtained for the EBN membranes in order to compare their performance to our previously published results for NR211, NR212, N115 and N117. 8 Charge and discharge polarization curves were obtained using a constant voltage staircase mode with 50 mV increments every 2 min.…”
Section: Wementioning
confidence: 99%